Lieu de tentation, espace du salut: le désert comme hétérotopie dans la Vie d’Antoine d’Athanase d’Alexandrie - Sághy, Marianne (Verbum – Analecta Neolatina, 2014)
This article aims to place the Athanasian desert on the list of Foucauldian heterotopiae. In Life of Antony, Athanasius of Alexandria creates a Christian desert in stark opposition with the political space of the Roman Empire dominated by heretical emperors. The desert is an agora of spiritual fight with demons, a meeting place with God as well as an ideological landscape shaped by Athanasius’ struggle with secular power. The desert’s claims to utopia as a “new Paradise” are built on the homogenizing bases of Nicaean orthodoxy.